In Quest of the Truth of Life. Review of Przemysław Zgórecki’s book, From Philosophy of Religion to Philosophy of Religious Experience. The Perspective of French Phenomenology (Poznań 2025) - Barbaszyński, Dariusz (Filozofia Chrześcijańska, 2025)
Review of Przemysław Zgórecki’s book, From Philosophy of Religion to Philosophy of Religious Experience. The Perspective of French Phenomenology (Poznań 2025).